The transformative experience of finding a relational home with a psychotherapist - Finlay, Linda; Hewitt Evans, Joanna (European Journal for Qualitative Research in Psychotherapy, 2022)
We explored the lived experience of finding a relational home in psychotherapy using a relational-centred, reflexive approach. Zoom dialogues, lasting between 35 minutes and 1.5 hours, were engaged with six psychotherapists concerning their experience of being a client and of finding a relational home. Our own experiences of being client, therapist and researcher were also explored. Phenomenologically orientated Reflexive Thematic Analysis iteratively processed the findings. Five emergent theme headings coalesced around: “Belonging”, “Safety”, “Holding”, “Affirmation”, and “Being-with”. Bridging concepts describing the nature of the relational home also emerged which linked and deepened the themes, namely: safe sanctuary, containing frame, secure base to grow, supporting connection, and spacious alliance. All participants experienced a relational home where they felt welcomed into a safe-enough space, attuned to, held, and appreciated by their solidly present, there-for-them therapist. In turn, this invited them to trust, let go and embrace more of themselves, and feel that they truly mattered. These findings are discussed in the light of the literature on philosophical understandings of home, as well as the therapy literature around the importance of relationship, presence, and relational depth. We also reflect on the implications for psychotherapy practice.